The molecular phylogenetics of the genus Oligoryzomys (Rodentia: Cricetidae) clarifies rodent host-Hantavirus associations - González Ittig, Raúl Enrique (2014)
Several species of the genus Oligoryzomys are natural hosts of different hantavirus genotypes affecting humans. The systematics of the genus is confusing, which complicates the identification of the rodent host and hence the potential endemic areas of hantavirus pulmonary syndrome. In this study, we analyse molecular data to infer phylogenetic relationships among Central and South American specimens of Oligoryzomys, and compare our results with previously published data on karyotypic, geographic distribution and host–virus associations to solve contradictory taxonomic reports. We identified 25 clades, each one corresponding to a different putative species. The phylogenetic trees show that Oligoryzomys longicaudatus is strongly related to the Oligoryzomys flavescens complex, which comprises four clades; Oligoryzomys nigripes is related to Oligoryzomys stramineus, Oligoryzomys vegetus is related to Oligoryzomys fulvescens from Central America, and Oligoryzomys brendae is the sister species of Oligoryzomys aff. destructor. We identified the following rodent host–hantavirus genotype relationships: O. longicaudatus–Andes; O. flavescens ‘West'–Bermejo; O. flavescens ‘East'–Lechiguanas; O. nigripes–Juquitiba; Oligoryzomys microtis–Rio Mamore and Rio Mamore-3; Oligoryzomys chacoensis–Oran; Oligoryzomys costaricencis–Choclo; Oligoryzomys delicatus–Maporal; Oligoryzomys utiaritensis–Castelo dos Sonhos; Oligoryzomys sp. RT2012–Rio Mamore-4; Oligoryzomys sp. (and not Oligoryzomys fornesi)–Anajatuba. This work, besides contributing to the development of prevention programmes for hantavirus epidemiology in Latin America, represents a comprehensive update of the systematics of the genus Oligoryzomys.